(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The purpose of this study is to evaluate the challenges encountered by police officers in the implementation of Republic Act 9165 in Barangay Bignay, Valenzuela City, in terms of community support, police officers, and intelligence. The respondent of the study is the selected police officer in VCPS Sub-station 7 Bignay to answer the questions presented in the study of challenges encountered in the implementation of Republic Act 9165. The target population is thirty (30) police officers in Barangay Bignay, Valenzuela City. This study gives the respondents and future researchers additional knowledge and information about the challenges encountered by police officers in implementation of Republic Act 9165, which helps to provide solutions to the given challenges. Future researchers could also explore and research the challenges encountered by police officers in the implementation of Republic Act 9165.